2023
DOI: 10.1007/s10490-023-09876-7
|View full text |Cite
|
Sign up to set email alerts
|

Shareholder reaction to corporate philanthropy after a natural disaster: an empirical exploration of the “signaling financial prospects” explanation

Abstract: Corporate response to natural disaster in the forms of cash and/or in-kind donations (corporate philanthropic disaster response, or CPDR) is a growing form of corporate philanthropy. Through an event study methodology based on 1,775 firms listed on the Tokyo Stock Exchange, we analyze shareholder reaction to CPDR announcements after the 2016 Kumamoto earthquakes in Japan. Controlling for the possibility that the most common explanations (buying goodwill and corporate governance) are at play, our results provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…As such, it holds significance in the field of business studies (Kitchen and Laurence, 2003). Existing research indicates that corporate philanthropy has a positive effect on stakeholders' impression (Azuma et al. , 2023) and corporate reputation (Brammer and Millington, 2005; Gardberg et al.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it holds significance in the field of business studies (Kitchen and Laurence, 2003). Existing research indicates that corporate philanthropy has a positive effect on stakeholders' impression (Azuma et al. , 2023) and corporate reputation (Brammer and Millington, 2005; Gardberg et al.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…First, serving as important internal stakeholders and a significant competitive asset for a company (Barney, 2001), employees are directly impacted by corporate philanthropic activities (e.g. Azuma et al. , 2023; Scheidler et al.…”
Section: Introductionmentioning
confidence: 99%
“…Brahmana, Puah, and Chai (2016) showed that credit ratings improved after the Nias tsunami in Indonesia. Another study by Azuma, Dahan, and Doh (2023) evaluated 1,775 listed companies on the Tokyo Stock Exchange following the Kumamoto earthquakes in Japan in 2016. The study found positive shareholder reactions to Corporate Disaster Relief (CDR) announcements.…”
Section: Theoretical Frameworkmentioning
confidence: 99%